Using of the Ampullaria glauca snails’ caviar for correction of the effects of the ionizing radiation exposure in small dose - L. V. Bal'-Prylypko; L. P. Derevyanko; N. M. Slobodyanyuk; E. R. Starkova; O. S. Androshchiuk (Ядерна фізика та енергетика)
Effectiveness of the use of Ampullaria glauca snails caviar for correction of radiation-induced disturbances after external disposable γ-irradiation of rats in dose of 2.0 Gy was investigated. Under these experimental conditions membrane stabilizing and adaptogenic properties of snails caviar have been established. Also, in rats that were irradiated at 2.0 Gy and consumed caviar of snails, normalization of the functional state of thyroid, pancreas and adrenal glands were revealed. Application of Ampullaria glauca snail caviar leads to modification of radiation damage and can be used to correct radiogenic disturbances in organism that is irradiated in small doses.